Environmental Impact Assessment (EIA) in Indonesian Law: Implementation and Effectiveness - Suprapto (Journal of Advanced Research in Social Sciences and Humanities, 2023)
Aim: This study examines the implementation and effectiveness of the Environmental Impact Assessment (EIA) process in Indonesia. The research aims to assess the outcomes of the EIA process by analyzing selected case studies across various sectors and regions. It also identifies contextual factors influencing EIA implementation and proposes recommendations to improve its effectiveness.Methodology: The current study employed a literature review approach to assess the implementation and effectiveness of Environmental Impact Assessment (EIA) in Indonesian law.Findings: The findings indicate positive outcomes in terms of impact identification and implementation of mitigation measures. However, challenges remain in stakeholder engagement, monitoring and enforcement, and integrating EIA outcomes into decision-making processes. To address these issues, recommendations are made, including strengthening the legal framework, promoting meaningful stakeholder engagement, enhancing capacity and expertise, integrating EIA outcomes into decision-making, and improving monitoring and compliance mechanisms. The study concludes by highlighting the need to consider Indonesia’s unique socio-political context and environmental challenges in improvingthe effectiveness of the EIA process.Implications/Novel Contribution: The current study provide insights into the challenges faced by Indonesia and propose contextually appropriate recommendations to enhance the effectiveness of the EIA process.